Treatment Result Following Fluoroscopic Guided Close Reduction and Internal Fixation by Per-Cutaneous Crossed K-Wires of Extension Type Gartland Type-II and Type-III Supracondylar Fracture of Humerus in Children - Kabir, Tafhim Ehsan; Humayun Kabir, ANM; Biswas, Alak Kanti; Anwar, Rahma Binte; Islam, Touhidul; Nath, Tusher Kanti (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background : Supracondylar fractures of the humerus is one of the most common fractures in children. Failure to treat properly leads to malunion of the fracture site. For that, closed reduction and percutaneous pinning is considered to be the golden choice for treatment. There are many methods in which percutaneous k-wire fixation can be done. The aim of this study is to report the advantages of percutaneous fixation using cross pinning from both medial and lateral sides. Materials and methods : A total number of seventy pediatric patients with Gartland type II and type III supracondylar fracture of the humerus were recruited from the outpatient department of two different hospitals between January 2018 and September 2020. All of them were treated using closed reduction and internal fixation using percutaneous crossed k-wires. The treatment outcomes were evaluated using Flynn’s criteria and were compared with other similar studies. Results : The mean age of study subjects was 8.14 ± 2.8 and the male to female ratio was 1.6:1. In 27(38.6%) cases the left arm was involved while in 43(61.4%) cases the right arm was involved. Preoperative complications included 1(1.4%) case with radial nerve palsy and 4(5.7%) cases with pulseless pink hand. When evaluating cosmetic outcome using Flynn’s criteria, there were 57(81.4%) excellent, 10(14.3%) good and 3(4.3%) fair outcomes. On evaluating outcome according to range of motion deficit outcomes were excellent in 35(50%), good in 22(31.4%), fair in 5(7.2%) and poor in 8(11.4%) children. Post-operative complications were 1(1.4%) ulnar nerve neuropraxia and 5(7.2%) superficial pin tract infections. Conclusion : Closed reduction and internal fixation using percutaneous crossed kwires placed from the medial and lateral side gives satisfactory cosmetic and functional outcomes in majority of the patients with Gartland type II and III supracondylar fractures of the humerus. Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 32-36